SWOT Analysis of the Development of Special Interest Tourism Cooking Class in Jehem Village, Bangli Regency, Bali - Arianty, A.A. Ayu Suwi; Arcana, Komang Trisna Pratiwi; Tunjungsari, Komang Ratih (Stupa, 2020)
In addition to natural attractions that are owned, the Village of Jehem also has a unique biological village that is biu batu. Biu batu is one type of banana that has many seeds in its flesh. The development of special interest tourism in Jehem Village needs to be analyzed regarding the sustainability of tourism activities. The purpose of this paper is to be able to know the weaknesses, strengths, opportunities, and challenges for the development of Jehem Village. The benefits of this paper are expected to be able to know its development strategy in the tourism industry competition in Bali. In this study using qualitative and quantitative data. Data collection in this study uses the method of observation and documentation. Through the SWOT analysis previously discussed, it can be concluded that making management promotion on social media, especially making websites more informative.